Gendering Globalized Flows in Bertrand Bonello’s Tiresia - Dokou, Christina (Amaltea. Revista de Mitocrítica, 2017)
Presented as the conciliatory voice of wisdom, Teiresias, the blind Theban seer who had been both man and woman, exemplifies how transcending gender can lead to a questioning of normative, victimizing cultural mandates within the polis. This gender-bending acquires further applications in Bertrand Bonello’s 2003 film, Tiresia, about the myth-informed travails of a transsexual Brazilian illegal immigrant prostitute in France. The film daringly deconstructs the dividing lines within contemporary globalized flows: immigrants vs. citizens, men vs. women, dogma vs. humanity. The performative gender of “Tiresia” exposes but also exacerbates the effects of cultural violence, yet also intimates peaceful alternatives.